1999
DOI: 10.1021/es981045r
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Incineration of 4-Chlorophenol and the Identification of Products and Intermediates by Mass Spectrometry

Abstract: This report summarizes results obtained as part of a larger effort to demonstrate the applicability of electrolytic procedures for the direct anodic (oxidative) degradation of toxic organic wastes. We refer to this process as "electrochemical incineration" (ECI) because the ultimate degradation products, e.g., carbon dioxide, are equivalent to those achieved by thermal incineration processes. In this work, the ECI of 4-chlorophenol is achieved in an aqueous medium using a platinum anode coated with a quaternar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(89 citation statements)
references
References 29 publications
2
85
0
2
Order By: Relevance
“…Electrochemical conversion and combustion seem to be environmentally friendly, because the only reagent used is electrical current, pH is neutral and mineralization is more extended than, for example, in the Fenton process. In general, electrodes for the oxidation of organic pollutants can be made from numerous materials [4][5][6][7]. However, for wide application of electrochemical degradation it is necessary to optimize electrolysis conditions, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical conversion and combustion seem to be environmentally friendly, because the only reagent used is electrical current, pH is neutral and mineralization is more extended than, for example, in the Fenton process. In general, electrodes for the oxidation of organic pollutants can be made from numerous materials [4][5][6][7]. However, for wide application of electrochemical degradation it is necessary to optimize electrolysis conditions, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover Johnson et al 32 demonstrated that phenol was degraded into intermediate compounds (benzoquinone and carboxylic acids) during the photoelectrochemical degradation. They observed that the solution color changed to light brown with benzoquinone generation and returned to its original colorless appearance with the gradual conversion of this substance into carboxylic acids.…”
Section: Discussionmentioning
confidence: 99%
“…The most useful direct electrochemical method is anodic oxidation (Kaba et al, 1990;Kotz et al, 1991;Stucki et al, 1991;Comninellis andPulgarin, 1991, 1993;Murphy et al, 1992;Comninellis and Nerini, 1995;Feng et al, 1995;Johnson et al, 1999;Gandini et al, 2000;Rodrigo et al, 2001;Rodgers and Bunce, 2001;Wu and Zhou, 2001) where organic compounds are essentially degraded by reaction with adsorbed hydroxyl radicals at the anode surface, which are generated from water oxidation:…”
Section: General Aspectsmentioning
confidence: 99%
“…Thus, although the traditional Pt anodes has been used for this purpose (Kaba et al, 1990;Kotz et al, 1991;Stucki et al, 1991;Comninellis andPulgarin, 1991, 1993;Murphy et al, 1992;Comninellis and Nerini, 1995), it are less efficient that the oxide-base electrodes such as PbO 2 (Kaba et al, 1990;Feng et al, 1995;Wu and Zhou, 2001), doped PbO 2 (Feng et al, 1995), doped SnO 2 Stucki et al, 1991;Comninellis andPulgarin, 1991, 1993;Johnson et al, 1999), IrO 2 (Comninellis and Nerini, 1995;Rodgers and Bunce, 2001) or more recently to the boron-doped diamond thin-layer anode, BDD (Gandini et al, 2000;Rodrigo et al, 2001). On the other hand, the indirect electrochemical methods involves the previous formation of oxidizing agents such as H 2 O 2 (Hsiao and Nobe, 1993;Do 1993Do , 1994Ponce de Leon and Pletcher, 1995;Brilla et al, 1996;Brillas et al, 1998;Alvarez-Gallegos and Pletcher, 1999;Harrington and Pletcher, 1999;Brillas et al, 2000;Oturan et al, 2000, Oturan, 2000Oturan et al, 2001):…”
Section: General Aspectsmentioning
confidence: 99%